Fatores influenciadores e resultados de projetos de inovação aberta em uma cooperativa de trabalho médico - Garboça, Everton Antonio (2021)
Open innovation consists of exploring knowledge from outside the organization, where internal and external agents work in synergy to improve processes and create new products and services, enhancing competitiveness and sustainability in organizations. The aim of this study was to analyze the influencing factors and the results generated by open innovation projects developed by a medical work cooperative. For this, this study had a qualitative approach, using the case study strategy, consisting of the definition of analysis groups, based on the literature, in the performance of documentary analysis and interviews with 12 internal and 7 external agents who participated in open innovation projects, executed by the organization in the last three years, the main ones being: two hackathons (development marathons) , partnerships with start-ups and the creation of an innovation hub in conjunction with Sebrae Cascavel and Unioeste. Within the group of influencing factors, related to the organizational structure, the results observed were a partial fulfillment of all items, evidencing that the cooperative can still implement sectors, teams and leaders focused on projects for the evolution of results. In the group of relationship networks, culture, and strategy, there was also a partial service in items such as processes, communication and incentives, which still have a structure and implementation with limitations. Still in this group, we highlight the item of relationship networks that had a result with total service, thus being a strong point identified within the dynamics of open innovation. In the innovative performance group, the non-attendance of the items of quantity of new products and the use of these products stood out. On the other hand, a positive highlight found is related to organizational gains, where the cooperative presented good results, with revenue recovery indicators of approximately R$ 500,000.00, with tools developed through open innovation projects. The group linked to market performance presented the worst results, with the non-attendance in several items, thus demonstrating another gap to be explored by the cooperative, especially with regard to the development of projects that propel the new products. Finally, the operational performance group showed a positive highlight in terms of quality and process improvement. Thus, it can be inferred that open innovation projects have several opportunities for improvement to be implemented in practically all the groups analyzed, but, considering that they are still projects with a short implementation time, they already demonstrate positive results and promising scenarios in the medium and long term. This research contributes in a practical way to the elaboration of strategies linked to the development of open innovation, producing more effective results for the organization and external audiences involved, such as innovation promotion agencies, start-ups and universities in the region, promoting the evolution of innovation in the regional context in which the cooperative is inserted. In addition, it offers a structured proposal for the analysis of open innovation, which can be replicated by other cooperatives in the health sector, cooperatives from other branches of activity and even other types of organization that develop projects or actions in this subject, aiming to achieve more effective results.